The right to access justice of people with disabilities in Vietnam in the context of globalization and international integration - Tran, Mộng Bình (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Access to justice is a fundamental human right enshrined in the Universal Declaration of Human Rights [1]. However, the right to access justice for people with disabilities still has certain limitations and inadequacies. With physical disabilities and the inferiority of people with disabilities, it is easy for people with disabilities to feel isolated in society and to find it arduous to access justice fairly. In this article, the author discusses the right to access justice for people with disabilities, the reality of applying the law and proposes several solutions to ensure better the right to access justice for people with disabilities in Vietnam in the context of globalization and international integration through legal tools such as the legal system for people with disabilities, the justice system; modern technology; initiative of people with disabilities and encourage other communities of people with disabilities to apply their right to access to justice.